Towards a complete study of central exclusive production of K+K− pairs in proton-proton collisions within the tensor Pomeron approach - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review, 2018)
We present a study of the central exclusive production of the K+K− pairs in proton-proton collisions at high energies. We consider diffractive mechanisms including the K+K− continuum, the dominant scalar f0(980), f0(1500), f0(1710) and tensor f2(1270), f′2(1525) resonances decaying into the K+K− pairs. We include also photoproduction mechanisms for the nonresonant (Drell-Söding) and the ϕ(1020) resonance contributions. The theoretical results are calculated within the tensor-Pomeron approach including both Pomeron and Reggeon exchanges. Predictions for planned or current experiments at RHIC and LHC are presented. We discuss the influence of the experimental cuts on the integrated cross section and on various differential distributions for outgoing particles. The distributions in two-kaon invariant mass, in a special “glueball filter variable,” as well as examples of angular distributions in the K+K− rest frame are presented. We compare the ϕ(1020) and continuum photoproduction contributions to the f0(980) and continuum diffractive contributions and discuss whether the ϕ(1020) resonance could be extracted experimentally. For the determination of some model parameters we also include a discussion of K-nucleon scattering, in particular total cross sections, and of ϕ(1020) photoproduction.
Gesehen am 25.02.2020
Im Titel sind die Zeichen "+" und "-" hochgestellt